'A Tactical Manoeuvre to Apply Pressure': Race and the Role of Public Inquiries in the 1980 Bristol 'Riot'. (3rd June 2017) - Peplow, Simon
Abstract: When violence erupted on the streets of England in 1981, it undoubtedly shocked the country in its scope and severity. However, such disorder had been foreshadowed when the St Pauls area of Bristol saw anti-police disturbances on 2 April 1980. This article focusses on the responses to this, from the local community and organizations as well as local and national government, which in the historiography has often been relegated to passing mentions prior to detailed discussion of the 1981 events. Utilizing recently released and understudied local records, it argues that appeals for a public inquiry from sections of the local community demonstrates the value awarded to them by this politically marginalized group, and the failings of other democratic forms of registering complaints. Public inquiries have long been a key component of the British constitutional system, allowing a unique public interaction with authorities—but it would take increased violence in Brixton the following year before establishment figures were sufficiently alarmed to grant one. This article argues that obtaining this government-endorsed response and an increased participation in the public discourse should be viewed as an aspect within a broader black civil rights movement, challenging claims that minorities played an underrepresented role in motivating advances. However, there was a clear division of attitudes towards public inquiries, demonstrating the moderate tactics utilized by local organizations and older generations, as opposed to more militant groups and the black youth who took to the streets.